2017
DOI: 10.1128/aac.02319-16
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Polymyxins: Is There Any Difference between Colistimethate and Polymyxin B?

Abstract: Nephrotoxicity is a common adverse effect of the clinically used polymyxins, colistin and polymyxin B. This adverse effect is dose limiting for both polymyxins, as the plasma polymyxin concentrations associated with renal damage overlap those required for antibacterial effect. Since development of acute kidney injury (AKI) during therapy is highly undesirable, it is extremely important to know whether there is any difference between the nephrotoxic potential of colistin (administered as its inefficient prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 50 publications
8
120
0
4
Order By: Relevance
“…The rate of good response to polymyxin B observed in this study should not related to the prior use of carbapenems or a combination of polymyxin B and carbapenems because all isolated bacteria from the patients were resistant to carbapenems and the results from the recent randomized controlled trial (RCT) revealed that the outcomes of the patients infected with XDR Gram-negative bacteria who received a combination of colistin and meropenem was not significantly better than those who received colistin alone 14. Regarding the nephrotoxicity of polymyxin B, the findings from our study were in accordance with the recent reviews reporting that polymyxin B was associated with less risk of nephrotoxicity than colistin 15,16…”
Section: Discussionsupporting
confidence: 89%
“…The rate of good response to polymyxin B observed in this study should not related to the prior use of carbapenems or a combination of polymyxin B and carbapenems because all isolated bacteria from the patients were resistant to carbapenems and the results from the recent randomized controlled trial (RCT) revealed that the outcomes of the patients infected with XDR Gram-negative bacteria who received a combination of colistin and meropenem was not significantly better than those who received colistin alone 14. Regarding the nephrotoxicity of polymyxin B, the findings from our study were in accordance with the recent reviews reporting that polymyxin B was associated with less risk of nephrotoxicity than colistin 15,16…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, plasma polymyxin B concentrations achieved among patients receiving the current upper limit daily dose are not likely to be reliably efficacious in many clinical scenarios including respiratory tract infections . Second, it is not possible to simply increase the daily doses of CMS or polymyxin B beyond doses recommended in this document due to the potential for nephrotoxicity that is the major dose‐limiting adverse effect . Third, the emerging body of evidence in preclinical lung infection models suggests poor in vivo response to the polymyxins when administered parenterally .…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%
“…Thus a lack of clarity remains about how optimally to utilize and dose colistin and polymyxin B . Unfortunately, polymyxins are highly nephrotoxic agents, and acute kidney injury (AKI) occurs frequently with conventional doses . Given the narrow therapeutic windows (low therapeutic indices) of polymyxins, this guideline provides clinicians with a practical framework for use in treating infections caused by MDR and XDR gram‐negative pathogens.…”
mentioning
confidence: 99%
“…With the increase in carbapenem‐resistant infections, colistin, a drug that was previously removed from the clinic due to high toxicity, has been reintroduced to the clinic. Colistin is far from an ideal drug, as 50–60% of people taking colistin experience acute kidney injury . Additionally, colistin resistance has emerged, and alarmingly the resistance can be easily spread via horizontal gene transfer of plasmids .…”
Section: Gram‐negative Bacteria As a Major Public Health Concernmentioning
confidence: 99%
“…Colistin is far from an ideal drug, as 50-60% of people taking colistin experience acute kidney injury. [37][38][39] Additionally, colistin resistance has emerged, and alarmingly the resistance can be easily spread via horizontal gene transfer of plasmids. [9][10][11]40 The first plasmid associated with colistin resistance was discovered in 2016 in China, 11 but has already spread throughout the world.…”
Section: Gram-negative Bacteria As a Major Public Health Concernmentioning
confidence: 99%